Analysis of human β‐papillomavirus and Merkel cell polyomavirus infection in skin lesions and eyebrow hair bulbs from a cohort of patients with chronic lymphocytic leukaemia. (26th October 2014) - Peretti, A.; Borgogna, C.; Rossi, D.; De Paoli, L.; Bawadekar, M.; Zavattaro, E.; Boldorini, R.; De Andrea, M.; Gaidano, G.; Gariglio, M.
Summary Background Research demonstrates an increased incidence of skin cancer in immunocompromised hosts, including patients with chronic lymphocytic leukaemia (CLL) and organ transplant recipients (OTRs). Active human β‐papillomavirus (β‐HPV) infection has been found in OTR skin lesions, suggesting its possible involvement in skin carcinogenesis. Merkel cell polyomavirus (MCPyV) has also been reported in cases of skin cancer. Objectives To investigate the potential correlations between patient clinical features and skin cancer development, and the presence of β‐HPV and MCPyV DNA and protein markers in skin lesions and hair bulbs from patients with CLL. Methods The clinical features of 293 patients with CLL were analysed according to the presence or absence of skin lesions. β‐HPV and MCPyV infection was investigated in skin lesions and hair bulbs from the study cohort by both polymerase chain reaction (PCR) analysis and immunohistochemical screening. Results No significant correlations were observed between any of the analysed haematological parameters and the development of skin cancer. PCR analysis revealed the presence of β‐HPV and MCPyV DNA in skin lesions, and 83% of positivity for MCPyV DNA in hair bulbs, while systematic immunohistochemical analysis of all the lesions failed to detect any expression of the viral proteins β‐HPV E4, L1 or MCPyV LTAg. Conclusions Overall, the data indicate that carriage of β‐HPV and MCPyV in the lesional skin and hair bulbs from patients with CLL without any evident reactivation at skin tumour sites most likely represents coincidental rather than causal infection. This contrasts with previous findings in relation to OTR‐derived skin lesions.